Modulatory effects of platelet-rich plasma on viral kinetics of BoAHV-1.1, BoGHV-4, and BVDV in bovine cell cultures: A proof-of-concept study - Andreoli, Valentina; Lopez, Sofia; Delgado, Santiago German; Perez, Sandra Elizabeth; Pereyra, Susana Beatriz; Gonzalez Altamiranda, Erika Analía; Romeo, Florencia; Grolli, Stefano; Verna, Andrea Elizabeth (Elsevier, 2026)
Reproductive viral diseases caused by Bovine alphaherpesvirus 1.1 (BoAHV-1.1), Bovine gam-maherpesvirus 4 (BoGHV-4), and Bovine viral diarrhoea virus (BVDV) impose a substantial economic burden on the cattle in dustry, primarily through infertility, abortion, and impaired reproductive performance. Owing to the limited efficacy of current antiviral strategies, this study evaluated the in vitro effects of platelet-rich plasma (PRP), at concentrations of 5 % and 10 %, on the replication kinetics of these viruses in Madin-Darby bovine kidney (MDBK) cells and primary bovine endometrial stromal cells (BESc). PRP modulated viral replication in a virus-, cell type-, and dose-related manner. In BoAHV-1.1-infected MDBK cells, 10 % PRP reduced extracellular titres but increases intracellular accumulation, suggesting interference with viral egress. In BESc, both intra- and extracellular titres decreased, consistent with a broader antiviral effect. For BoGHV-4 and BVDV, PRP induced variable and time-dependent responses across cell types. These results demonstrate that PRP can influence bovine viral replication dynamics in vitro and support further investigations into its mechanistic basis and in vivo therapeutic potential.